Variations in the leaf metabolite profile between hydroponic and field grown MoringaoleiferaLam. genotypes. (August 2021) - Managa, Lavhelesani R.; du Toit, Elsa S.; Prinsloo, Gerhard
Abstract: Medicinal and herbal plants are increasingly cultivated on commercial scale all around the world, to satisfy the large demand for natural remedies associated with plant bioactive compounds. Moringa oleifera Lam. is one of these attractive plant species, being cultivated across the world, with most of the production in Africa and Asia. However, it is increasingly reported that the composition and concentration of bioactive compounds in medicinal plants, are largely influenced by factors such as the growing environment, harvesting time, and climatic factors among others. The aim of this study was therefore to determine the differences in the leaf metabolite profile between hydroponic and field grown M. oleifera plants due to cultivation system, harvesting time and genotypes. 1 H NMR was used for data acquisition, and MestReNova software was used for the pre-processing of the spectral data. Multivariate data analysis by means of PCA and OPLS-DA was conducted, followed by targeted metabolite analyses. The results show variations in the leaf metabolite profile as influenced by cultivation systems, harvesting time and genotypes. In both PKM-1 and Malawi hybrid genotypes, the concentration level of chlorogenic acid, ferulic acid, vanillic acid, and wogonin compounds were higher in the hydroponic leaf material, whereas the concentration level of esculetin, niazirin and GABA were slightly higher in the field harvested leaf materials. With regards to harvesting time effect, the concentration level of all seven targeted compounds were higher in February (summer) harvest as compared to May (autumn) harvest. Among the genotypes, PKM-1 showed to have higher concentration of certain targeted compounds as compared to Malawi hybrid, but on the other hand certain compounds from the Malawi hybrid showed also higher concentrations. These results provide insight on the possible alternative production system that can be adopted to optimise and improve accumulation of bioactive compounds in M. oleifera leaf materials. Highlights: Moringa oleifera Lam. is one of the world's most useful medicinal plants 1 H NMR analysis revealed changes in the leaf metabolite profile of M. oleifera genotypes due to seasonal change and cultivation system Compounds such as chlorogenic acid, ferulic acid, vanillic acid, wogonin, esculetin, niazarin and GABA showed an increase in concentration in summer harvesting as compared to autumn harvesting Concentration level of chlorogenic acid, ferulic acid, vanillic acid, and wogonin compounds were also higher in the hydroponic leaf material as compared to field harvested materials